THE INFLUENCE OF INTELLECTUAL CAPITAL ON THE COMPANY FINANCIAL PERFORMANCE - Devi, Bunga Ekawati; Khairunnisa, Khairunnisa; Budiono, Eddy (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2017)
Global economic conditions makes competition between bussinesses more competitive. Kinds of innovations and intense competition forcing the company to change the pattern of management, from labor based business to knowledge based business. The approach used in the research and measurement of knowledge assets are intellectual capital. This research uses the intellectual capital measurements with Pulic?s method using Value Added lntellectual Coefficient (VAICTM) by forming components are Value Added lntellectual Coefficient (VAICTM) dengan komponen pembentuk intellectual capital yaitu Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA). This research aims to know the influence of intellectual capital on company financial performance with proxy Return on Assets (ROA).This research type is causality verificative descriptive research. The unit of analysis in this study is a company of Electronic, Automotive and Components Listed in Indonesian Stock Exchange (IDX). Data were selected using purposive sampling techniques so acquired 11 companies over five years of research from 2011 to 2015. Hypothesis test use path analysis. The results show that VACA and STVA partially had a positive significant influence on company financial performance. While VAHU had no influence on company financial performance. The simultaneously show that VACA, VAHU, and STVA had a positive significant influence in company financial performance. Keywords :Intellectual Capital, VAICTM, Company Financial Performance, and ROA